1994
DOI: 10.1007/bf03257402
|View full text |Cite
|
Sign up to set email alerts
|

Vecuronium Pharmacokinetic-Pharmacodynamic Modelling With and Without a Receptor Concentration in the Effect Compartment in Anaesthetised Patients

Abstract: The pharmacokinetic-pharmacodynamic (PK-PD) relationship of vecuronium administered as a 0.1 mg/kg intravenous bolus was evaluated during both the onset of and recovery from neuromuscular block in 9 anaesthetised patients. Sigmoid Emax modelling of neuromuscular block versus vecuronium effect compartment concentrations indicated comparable effective concentrations at 50% block (EC 50 ) for both onset and recovery (146 ± 12 vs 144 ± 13 ng/ml, respectively).However, during onset, the sigmoid was systematically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The sampling frequency also has an impact on PK/PD parameter estimation, and the magnitude of the effect varies depending on the type of analysis. For example, k e0 values obtained using early intensive sampling can be up to 50% smaller than those obtained with a traditional sampling scheme using a non‐compartmental PK model after a bolus dose of vecuronium ( 49). Alternatively, when compartmental analysis of traditional data sets is compared with non‐compartmental analysis of early intensive sampling data sets, EC 50 values are similar, which suggests that both approaches are valid for the drug in question ( 48, 50).…”
Section: Test Drug Administration Sampling and Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…The sampling frequency also has an impact on PK/PD parameter estimation, and the magnitude of the effect varies depending on the type of analysis. For example, k e0 values obtained using early intensive sampling can be up to 50% smaller than those obtained with a traditional sampling scheme using a non‐compartmental PK model after a bolus dose of vecuronium ( 49). Alternatively, when compartmental analysis of traditional data sets is compared with non‐compartmental analysis of early intensive sampling data sets, EC 50 values are similar, which suggests that both approaches are valid for the drug in question ( 48, 50).…”
Section: Test Drug Administration Sampling and Analysismentioning
confidence: 94%
“…One parameter describes the concentration associated with an effect of 0.5 (EC 50 ), the other the sigmoidicity of the concentration versus effect curve (γ). The general form of the relationship is ( 49, 68):…”
Section: Pharmacokinetic/pharmacodynamic (Pk/pd) Modelingmentioning
confidence: 99%
“…1,16 Our results imply that in rats, the differences in clearance between the three enantiomers are less marked than in humans. 5 On the basis of these considerations and from the results obtained in this study, the use of a short infusion seems to be suitable to characterize the PK-PD relationships of mivacurium. Differences in plasma cholinesterase activity and/or concentrations between both species are likely to be the reason for the differences encountered; differences in plasma esterase activity between humans and various animal species have been reported previously.…”
Section: Discussionmentioning
confidence: 82%
“…The data in Figures 1 and 2 show that the decay in the neuromuscular effect follows closely the decay in total mivacurium in plasma; therefore, in rats, the time course of total mivacurium in plasma reflects the time course of the active enantiomers. 5 We selected the short infusion administration based on the results found by Ducharme et al 5 who showed that analysis from pooled onset and recovery data when there is a preponderance of recovery data (i.e., after a bolus injection) could lead to PD estimates that are different from those obtained from the analyses that used onset or recovery data alone. 1,16 Our results imply that in rats, the differences in clearance between the three enantiomers are less marked than in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation